The Design of the Eurosystem$1 (Bs Monetary Policy Instrumentss - Neyer, Ulrike; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2007)
The creation of a single monetary currency and a single monetary policy in the euro area has faced extraordinary challenges, among them the design of suitable monetary policy instruments. This book evaluates monetary policy instruments of the Eurosystem against a number of requirements. For doing so, a theoretical model framework is developed which brings together the monetary policy activities of a central bank and the liquidity management of banks considering the main characteristics and institutional features of the euro area. Main results of this analysis are that different costs of obtaining liquidity directly from the central bank can explain the existence of an interbank market in the euro area and the positive spread between the interbank market rate and the repo rate; that the redesign of the Eurosystem$1 (Bs instruments in 2004 has to be evaluated positively and that a further change to the minimum reserve system would enhance the flexibility of monetary policy in the euro area.s
Monetary Policy Instruments of the Eurosystem -- Stylized Facts and First Explanations -- Base Model: Banks$1 (BLiquidity Management and Interbank Market Equilibrium -- Remuneration of Required Reserves at the Current Repo Rate -- Remuneration of Required Reserves at an Average Rate -- Overlapping Maturities of Central Bank Credits -- Implications for the Eurosystem$1 (Bs Operational Framework -- Summary.s
Keywords: Macroeconomics; European Economic Community literature; Economic policy; Economics; Macroeconomics/Monetary Economics//Financial Economics; European Integration; Economic Policy; Electronic books